Heart regeneration with human pluripotent stem cells: Prospects and challenges - Jiang, Yuqian (Bioact Mater, 2020)
Cardiovascular disease, ranging from congenital heart disease to adult myocardial infarction, is the leading cause of death worldwide. In pursuit of reliable cardiovascular regenerative medicine, human pluripotent stem cells (hPSCs), including human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs), offer plenty of potential cell-based applications. HPSCs are capable of proliferating indefinitely in an undifferentiated state, and are also pluripotent, being able to differentiate into virtually any somatic cell types given specific stepwise cues, thus representing an unlimited source to generate functional cardiovascular cells for heart regeneration. Here we recapitulated current advances in developing efficient protocols to generate hPSC-derived cardiovascular cell lineages, including cardiomyocytes, endothelial cells, and epicardial cells. We also discussed applications of hPSC-derived cells in combination with compatible bioactive materials, promising trials of cell transplantation in animal models of myocardial infarction, and potential hurdles to bring us closer to the ultimate goal of cell-based heart repair.